Assessment of summertime ozone formation in the Sichuan Basin, southwestern China - Yang, Xianyu; Yang, Tong; Lu, Yaqiong; Jiang, Mengjiao; Zhang, Shaobo; Shao, Ping; Yuan, Liang; Wang, Chao; Wang, Lei (Frontiers in Ecology and Evolution, 2022)
The alarming increase of ambient ozone (O3) levels across China raises an urgent need in understanding underlying mechanisms of regional O3 events for highly urbanized city clusters. Sichuan Basin (SCB) situated in southwestern China has experienced severe O3 pollution at times in summer from 2013 to 2020. Here, we use the WRF-CMAQ model with the Integrated Source Apportionment Method (ISAM) to investigate the evolution mechanism and conduct source attribution of an extreme O3 episode in the SCB from June 1 to 8, 2019. This typical summer O3 episode is associated with the synoptic-driven meteorological phenomenon and transboundary flow of O3 and precursors across the SCB. Weak ventilation in combination with stagnant conditions triggered the basin-wide high O3 concentrations and enhanced BVOC emissions substantially contribute up to 57.9 μg/m3 MDA8 O3. CMAQ-ISAM indicates that precursor emissions from industrial and transportation have the largest impacts on elevating ambient O3 concentrations, while power plant emissions exhibit insignificant contributions to basin-wide O3 episodes. These results improve the understanding of the summertime O3 episode in the SCB and contribute insights into designing O3 mitigation policy.